Autonomous navigaation system - Nah, Zheng Rong (Nanyang Technological University, 2023)
The Inertial Measurement Unit (IMU) plays an important role in Simultaneous Localization and Mapping (SLAM) systems. The IMU provides information about the vehicle’s orientation and movement and together with other sensor information from cameras, LiDAR etc., the SLAM algorithm can perform precise mapping of the environment and accurate estimation of the device's position and trajectory. In this project, the author aims to develop an IMU initialization method that can be performed while the IMU remains stationary. The IMU initialization method of the ORB-SLAM3 system was modified to allow the IMU to be initialized while stationary, for both the stereo and monocular SLAM systems.